Enhanced photoelectrochemical performance from particulate ZnSe:Cu(In, Ga)Se2 photocathodes during solar hydrogen production via particle size control. Issue 2 (5th October 2020) - Takagi, Fumiaki; Kageshima, Yosuke; Teshima, Katsuya; Domen, Kazunari; Nishikiori, Hiromasa
Abstract : The photoelectrochemical performance of a particulate (ZnSe)0.85 (CuIn0.7 Ga0.3 Se2 )0.15 photocathode was enhanced via a facile classification method. Abstract : (ZnSe)0.85 (CuIn0.7 Ga0.3 Se2 )0.15 (ZnSe:CIGS) photocatalytic particles are a promising candidate material for photocathodes in sunlight-driven photoelectrochemical (PEC) hydrogen evolution systems responsive up to 800–850 nm. However, the ZnSe:CIGS particles used in prior studies had wide particle size distributions, on the order of submicrons to microns. Thus, it may be possible to improve the PEC activity by controlling particle size, rather than the conventional surface modification and/or optimization of synthesis conditions. In the present study, ZnSe:CIGS particles synthesized via a flux method were classified into three categories with average particle sizes of 14.2 μm (large), 4.46 μm (middle) and 1.09 μm (small), and the origin of the particle size effect on PEC performance was examined using electrochemical techniques. A particulate photocathode made using the middle ZnSe:CIGS particles exhibited higher cathodic photocurrent than one made of the original unclassified material, while the small and large particles showed inferior performances. Stripping voltammetry demonstrated that the larger particle size increased the specific surface area of the semiconductor particles on the photoelectrode surface and also increased the electrochemically active surface area of the Pt. Electrochemical impedance spectroscopy indicated that the carrier density and flat-band potential values of the small and middle particles were similar, whereas the large particles showed a low carrier density and a negative flat-band potential shift. Increasing the particle size increased the resistance of the bulk particulate semiconductor, possibly suppressing migration of the majority carriers to the back contact layer. The data indicate that the particle size dependence of the PEC properties of particulate ZnSe:CIGS photocathodes can be attributed to the effects of specific surface area, carrier density and bulk resistance.